PSYCHOLOGICAL FOUNDATIONS OF DEVELOPING ENGLISH READING COMPETENCE IN 5TH–6TH GRADE STUDENTS - Xabibovna, Mashrapova Sevara (Research Focus International Scientific Journal, 2026)
This article discusses the psychophysiological characteristics of 5th–6th grade students and their importance in the formation of reading competence in a foreign language. It also analyzes the methodological foundations of developing text comprehension and analysis skills in accordance with the requirements of international PISA and PIRLS studies. This article examines the fundamental psychophysiological and pedagogical-psychological foundations of developing English reading competence in 5th–6th grade students in the modern educational paradigm. The relevance of the study is determined by the integration of the Uzbek education system with the requirements of international assessment programs, in particular, PIRLS, which measures literacy at the junction of primary and secondary education, and PISA, which focuses on functional literacy. The article analyzes the stages of cognitive development of 11–12-year-old students - the period of transition from concrete thinking to abstract-logical observation. The author interprets the reading process as a complex cognitive activity, not just decoding (letter and sound correspondence). The research highlights the role of psychological concepts such as the "zone of proximal development", "metacognitive monitoring" and "scaffolding" in the formation of students' skills in interpreting the text, analyzing the author's position and transferring information to a real-life context. The practical part of the article puts forward methodological recommendations on increasing students' motivation to read in English lessons, overcoming psychological barriers such as "fear of not understanding" (reading anxiety), and using the possibilities of visualization and associative memory when working with text. In conclusion, it is proven that the systematic development of reading competence is the main factor in bringing not only the student's linguistic wealth, but also his intellectual potential and critical thinking level to international standards.